Adolescent pregnancy and rural health: An experience report - Andres, Silvana Carloto; Machado, Liane Bahú; Kleinubing, Rachel Einloft; Cabral, Thaynan Silveira; Lima, Jozéli Fernandes de; Borges, Mariana Camargo; Gomes, Iris Elizabete Messa; Freitas, Eva Inês Vilanova Ribeiro; Bassin , Gloria Cogo; Reginaldo, Marjana Pivot (Seven Editora, 2023)
Adolescence is a period that results in a series of transformations, among which sexual initiation stands out. Given this, there is an increase in the incidence of pregnancy in this period. This situation has been considered a public health problem due to the maternal-fetal risks that can be triggered by early pregnancy, in addition to dropping out of school and social problems. These risks can affect the lives of the adolescent and the baby and in the obstetric, psychosocial and economic spheres. This is an experience, descriptive and reflective report about the experience of nurses in the rural health unit in a city in the interior of Rio Grande do Sul about the prenatal care of pregnant adolescents. In order to discuss the experience of nurses, the results will be presented and a discussion of them with theoretical foundation interpreted and analyzed, emerging the following category: Pregnancy in adolescence and its implications in social, professional, school, and rural health life. Obstetric and fetal risks will only be reduced when there is a support network directed to adolescents, which focus on reproductive care, assiduous prenatal care and psychological and social support, involving health professionals, the school environment and family members. DOI:https://doi.org/10.56238/alookdevelopv1-177